Crystal structure of 4-(1-methyl-1-mesitylcyclobutane-3-yl)-2-aminothiazole - Aksoy, I; Yilmaz, I; Sari, U; Güven, K; Çukurovali, A (Wiley-V C H Verlag Gmbh, 2006)
The crystal structure of 4-(1-methyl-1-mesityleyclobutane-3-yl)-2-aminothiazole (C17H22N2S1) has been determined by X-ray crystallographic techniques. The compound crystallizes in the triclinic space group P-1 with Z = 6. The crystal structure was solved by direct methods and refined by full-matrix least squares to a final R-value of 0.052 for 2298 observed reflections [I > 2 sigma (I)]. There are three crystallographically independent molecules, I, II and III. These molecules are held together by intermolecular N-H...N hydrogen bonds.
Keywords: X-ray crystallography; crystal structure; aminothiazole; biological activity